PENERAPAN METODE TUTOR SEBAYA UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA HINDU PADA SISWA KELAS IV UPT SP SD NEGERI 152 KALAENA KIRI II - GUNA, I MADE MERTA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
This research was motivated by the low learning outcomes of Hindu Religious Education for class IV UPT SP students at SD Negeri 152 Kalaena Kiri II. Most students have not achieved minimum completeness in Hindu religious education lessons. This research aims to improve the learning outcomes of Hindu Religious Education for class IV students at UPT SP SD Negeri 152 Kalaena Kiri II by applying the peer tutoring method. This research is Classroom Action Research (PTK) , which was carried out in 2 cycles. The subjects in this research were 7 class IV students at UPT SP SD Negeri 152 Kalaena Kiri II for the 2023/2024 school year. Data analysis in this research used quantitative descriptive. The results of the research showed that student learning outcomes in cycle I had an average score of learning outcomes in the low category. The average value of student learning outcomes in cycle I was 71.42% classical completeness, 76.42% absorption capacity. Then in cycle II there was an increase, the average learning outcome for classical completeness became 85.7% and absorption capacity became 81.85%. The results of the analysis of the first cycle of students' interest in learning were high. And the results of the analysis of the learning outcomes of cycles I and II experienced an increase in the average value of learning outcomes by %, classical completeness was 4%, the absorption capacity was 14.28% with the use of the tutor method peer. Based on the results of this research, it can be concluded that the use of peer tutors can improve learning outcomes in Hindu Religious Education. Suggestions are made to related parties as follows (1) Hindu Religious Education Teachers should try to implement the use of peer tutors (2) Other researchers are expected to conduct further research related to the application of innovative learning models. ABSTRAKPenelitian ini dilatarbelakangi oleh rendahnya hasil belajar Pendidikan Agama Hindu siswa kelas IV UPT SP SD Negeri 152 Kalaena Kiri II. Sebagian besar siswa belum mencapai ketuntasan minimal pada pelajaran pendidikan agama Hindu.Penelitian ini bertujuan untuk meningkatkan hasil belajar Pendidikan Agama Hindu siswa kelas IV di UPT SP SD Negeri 152 Kalaena Kiri II dengan penerapan metode tutor sebaya.Penelitian ini merupakan Penelitian Tindakan Kelas (PTK),yang dilaksanakan dalam 2 siklus.Subyek dalam penelitian ini siswa kelas IV di UPT SP SD Negeri 152 Kalaena Kiri II tahun pelajaran 2023/2024 sebanyak 7 orang. Analisis data dalam penelitian ini menggunakan deskriftif kuantitatif .Hasil penelitian menunjukkan hasil belajar siswa pada siklus I skor rata-rata hasil belajar dengan kategori rendah. Nilai rata-rata hasil belajar siswa pada siklus I yaitu dengan ketuntasan klasikal 71,42 %,daya serap 76,42 %.Kemudian pada siklus II mengalami peningkatan ,rata-rata hasil belajar menjadi ketuntasan klasikal menjadi 85,7 % dan daya serap menjadi 81,85%.Hasil analisis siklus I minat belajar siswa tinggi .Dan hasil analisis hasil belajar siklus I dan II mengalami peningkatan nilai rata-rata hasil belajar sebesar %,ketuntasan klasikal sebesar 4 % daya serap sebesar 14,28% dengan penggunaan metode tutor sebaya. Berdasarkan hasil penelitian ini dapat disimpulkan penggunaan tutor sebaya dapat meningkatkan hasil belajar Pendidikan Agama Hindu. Diajukan saran kepada pihak terkait sebagai berikut (1)Guru Pendidikan Agama Hindu agar mencoba menerapkan penggunaan tutor sebaya(2)Peneliti lain diharapkan mengadakan penelitian lanjutan terkait dengan penerapan model pembelajaran yang inovatif.